Pemodelan Spasial Kasus Demam Berdarah Dengue (DBD) Menggunakan Geographically Weighted Regression (GWR) di Kota Bandung Tahun 2024 - Achmad Fadhilah; Desti Meirisa Putri; Sypa Septiani; Ameliya Ameliya (Universitas Pendidikan Ganesha, 2026)
The number of Dengue Hemorrhagic Fever (DHF) cases in Bandung City increased significantly in 2024, reaching 7,146 cases (four times higher than in 2023). The increase in DHF cases in an area is influenced by various factors, including geographic, sociodemographic, and environmental conditions. DHF cases is also influenced by the ecological conditions of the surrounding area, so it is necessary to consider the neighborhood features in the analysis of DHF case in a certain location. This study aims to build spatial modelling of DHF cases in Bandung City using Geographically Weighted Regression (GWR). GWR modeling works based on the local relationship between the independent variable (X) and the dependent variable (Y) and considers its surrounding area. The independent variables used in this study include elevation (X1), the number of children aged 5-14 years (X2), population density (X3), percentage of built-up area (X4), and road density (X5). Meanwhile, the dependent variable used is the number of DHF cases in Bandung City from January to April 2024. The GWR prediction results indicate that DHF cases are concentrated in the northern and southeastern regions of Bandung, with a global R² value of 0.778 (indicating that 77.8% of the variance is explained by the model). The variables that play a significant role in the GWR model of DHF cases in this study are altitude and the number of residents aged 5-14 years.